The roles of antioxidants and fatty acids in sperm cryopreservation - Yimer, Nurhusien; Yusoff, Rosnina; Haron, Abd Wahid; Kaka, Asmatullah (InTech, 2016)
Despite research developments in the area of sperm storage, it has become inevitable to realize a marked reduction in the quality of fresh semen following cryopreservation. As a result, research has continued and will also continue in the future looking forward for a much better and improved methods of sperm cryopreservation along with better understanding of the physical and biochemical challenges that the sperm has to face to survive during freezing. Among the various attempts made to improve the cryopreservation process and subsequently result in superior quality of sperm after thawing include manipulating the composition of semen extenders by addition of exogenous products including antioxidants and fatty acids. While fatty acids are added to strengthening plasma membrane stability, Antioxidants are incorporated to compensate the reduction in the endogenous antioxidants level of seminal plasma due to dilution as well as to combat with the excess reactive oxygen species (ROS) production during freezing. In this chapter, the roles of antioxidants and fatty acids in mammalian sperm cryopreservation, both from endogenous and exogenous perspectives, will be discussed with reference to the latest research findings.